Ação de ninhos de espuma de anuros e da sua microbiota associada na quitridiomicose - Bezerra, Saulo Gonçalves de Santiago (2021)
Chytridiomycosis is responsible for the decline of hundreds of amphibian species worldwide and the main infectious agent is the fungus Batrachochytrium dendrobatidis (Bd). One of the strategies to contain this disease is the enrichment of skin amphibia bacteria that are able to inhibit the growth of this fungus. Despite several studies regarding the influence of abiotic and biotic factors to the disease dynamics, the contribution of frog foam nest components in this complex host-parasite interaction is still unknown. These biofoams are composed of a complex mixture of carbohydrates and proteins, in addition to hosting a vast species-specific microbiota. In this sense, the goal of this study is to evaluate the effect of the foam nests produced by leptodactylid frogs and its associated microbiota on the Bd, as well as to identify a microbial inoculant with potential against this fungus. For this study, the fluid of foam nests from six frog species and bacteria isolated from the foam were tested against Bd. The unprecedented results show that foam nests biomolecules stimulate Bd growth, possibly being used as nutrients, and select different bacterial compositions. The culture-dependent microbiota is mostly composed of representatives of the phyla Proteobacteria, Bacteroidetes, Actinobacteria and Firmicutes. Among these isolates, eight had anti-Bd activity, with the most frequent genera being Pseudomonas and Enterobacter. The simulation of bioaugmentation in Leptodactylus vastus foam nests fluid in natura (non-sterile) showed (p < 0,05) that the inoculation of approximately 108 cells/mL of the Pseudomonas sp. P54 inhibits the fungus growth. This result is promising and extends the recognized anti-Bd potential of Pseudomonas spp., also present in frog skin microbiota, to foam nests.